Spatial distribution of rare earth elements in seawater and sediments, and bioaccumulation in plankton from the Yellow Sea - Hyeryeong Jeong; Chaehwan Park; Myung-Jin Hyun; Garam Kim; Howon Lee; Donghan Choi; Kongtae Ra (Marine Pollution Bulletin, 2026)

Evaluation of seasonal variations in energy sources and trophic positions of Calanus sinicus and Euphausia pacifica in the central-eastern Yellow Sea using bulk and compound-specific stable isotope analyses - Jiseung Kang; Yeonjung Lee; Dong Han Choi; Jae Hoon Noh; Howon Lee; Hyung-Ku Kang; Garam Kim; Kongtae Ra; Myung Jin Hyun; Won Seok Yang; JongSeok Won; Bohyung Choi; et al. (Marine Pollution Bulletin, 2026)

Spatial and Temporal Variation of Synechococcus Abundance and Diversity in the Yellow Sea - Jongseok Won; Myungjin Hyun; Wonseok Yang; Howon Lee; Yeonjung Lee; Seok Lee; Kongtae Ra; Hee Cheol Yang; Jae Hoon Noh; Dong Han Choi (Ocean Science Journal, 2025)

Impacts of Typhoon Bavi on Prokaryotic Communities in the Yellow Sea - Wonseok Yang; Myung Jin Hyun; Jae Hoon Noh; Yeonjung Lee; JongSeok Won; Howon Lee; Kongtae Ra; Dong Han Choi (Ocean Science Journal, 2024)

Preliminary Estimation of Protist Predation Potential on Picoplankton in Summer of the Yellow Sea - Young-Ok Kim; Mutsuo Ichinomiya; Jungmin Choi; Dong Han Choi; Wonseok Yang; Kyung-Hee Oh; Kongtae Ra; Howon Lee (Ocean Science Journal, 2024)

Phytoplankton spring succession pattern in the Yellow Sea surveyed at Socheongcho Ocean Research Station - Myung Jin Hyun; Dong Han Choi; Howon Lee; Jongseok Won; Go-Un Kim; Yeonjung Lee; Jin-Young Jeong; Kongtae Ra; Wonseok Yang; Jaeik Lee; Jongmin Jeong; Charity Mijin Lee; et al. (Frontiers in Marine Science, 2023)
The spring phytoplankton bloom is a critical event in temperate oceans typically associated with the highest productivity levels throughout the year. To investigate the bloom process in the Yellow Sea, daily data on physical, chemical, and phytoplankton taxonomic group biomass, calculated via the chemotaxonomic approach, were collected from late March or early April to late May between 2018 and 2020 at the Socheongcho Ocean Research Station. During early spring (late March to mid-April), phytoplankton biomass increased, accompanied by a decrease in nutrient levels, with Bacillariophyceae and Cryptophyceae being the dominant groups. As water temperature increased, a pycnocline began to develop in late April, leading to a peak of the phytoplankton bloom dominated by chlorophytes and Cryptophyceae. Network analysis suggested that this phytoplankton bloom was caused by the onset of vertical stratification induced by increased sea surface temperature. The chlorophyte peak induced phosphate limitation above the pycnocline, resulting in succession to Prymnesiophyceae and Dinophyceae. Following pycnocline formation, phytoplankton biomass below the pycnocline was dominated by Bacillariophyceae and Cryptophyceae, with decreasing or fluctuating trends depending on phosphate concentration. Apart from these general patterns, 2019 and 2020 both had distinctive traits. The 2019 data revealed lower phosphate concentrations than the other 2 years, leading to a smaller chlorophyte peak at the surface compared to 2018 and extreme phosphate limitation above the pycnocline. This limitation resulted in decreased biomass of late successional groups, including Prymnesiophyceae and Dinophyceae. Pycnocline formation was delayed in year 2020, and stratification was significantly weaker compared to the previous 2 years. Due to the pycnocline delay, the surface chlorophyte peak did not develop and no succession to late successional groups was observed. Instead, high levels of Bacillariophyceae and Cryptophyceae biomass were observed throughout the water column with no surface bloom. Thus, among various environmental factors, increasing surface water temperature and phosphate concentrations play pivotal roles in shaping phytoplankton bloom dynamics. Distinct yearly variation points to the broader impacts of climate shifts, emphasizing the need for continued marine monitoring.

A CHEMTAX Study Based on Picoeukaryotic Phytoplankton Pigments and Next-Generation Sequencing Data from the Ulleungdo–Dokdo Marine System of the East Sea (Japan Sea): Improvement of Long-Unresolved Underdetermined Bias - Myung Jin Hyun; Jongseok Won; Dong Han Choi; Howon Lee; Yeonjung Lee; Charity Mijin Lee; Chan Hong Park; Jae Hoon Noh (Journal of Marine Science and Engineering, 2022)
The CHEMTAX program has been widely used to estimate community composition based on major pigment concentrations in seawater. However, because CHEMTAX is an underdetermined optimization algorithm, underdetermined bias has remained an unsolved problem since its development in 1996. The risk of producing biased results increases when analyzing the picophytoplankton community; therefore, this study tested a new method for avoiding biased CHEMTAX results using the picophytoplankton community around the East Sea (Japan Sea). This method involves building a linear model between pigment concentration data and community composition data based on DNA sequencing to predict the pigment range for each operational taxonomic unit, based on the 95% prediction interval. Finally, the range data are transformed into an initial ratio and ratio limits for CHEMTAX analysis. Three combinations of initial ratios and ratio limits were tested to determine whether the modeled initial ratio and ratio limit could prevent underdetermined bias in the CHEMTAX estimates; these combinations were the modeled initial ratio and ratio limit, the modeled initial ratio with a default ratio limit of 500 s, and an initial ratio from previous research with the default ratio limit. The final ratio and composition data for each combination were compared with Bayesian compositional estimator-based final ratio and composition data, which are robust against underdetermined bias. Only CHEMTAX analysis using the modeled initial ratio and ratio limit was unbiased; all other combinations showed significant signs of bias. Therefore, the findings in this study indicate that ratio limits and the initial ratio are equally important in the CHEMTAX analysis of biased datasets. Moreover, we obtained statistically supported initial ratios and ratio limits through linear modeling of pigment concentrations and 16s rDNA composition data.

Next-generation sequencing reveals the diversity of benthic diatoms in tidal flats - Sung Min An; Dong Han Choi; Howon Lee; Jung Ho Lee; Jae Hoon Noh (Algae, 2018)

Spatial distribution of cold-adapted Synechococcus during spring in seas adjacent to Korea - Dong Han Choi; Jae Hoon Noh; Sung Min An; Yu Ri Choi; Howon Lee; Kongtae Ra; Dongseon Kim; TaeKeun Rho; Sang Heon Lee; Kyung-Tae Kim; Kyung-Il Chang; Jung Ho Lee (Algae, 2016)